Gallbladder volvulus mimicking a cardiac event - an unusual presentation - Basilie Teoh; Nicole Campbell; Paul Flanagan; Ian Campbell (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Gallbladder volvulus (GV) is a rare surgical emergency in which the gallbladder twists on its pedicle and becomes gangrenous. It most commonly presents with symptoms similar to acute cholecystitis. Investigations are seldom diagnostic, with both pathology tests and imaging often unremarkable, and as such it is often diagnosed intraoperatively. Given the potential consequence of a ruptured gallbladder leading to biliary peritonitis, it is an important condition to consider and suspected cases should proceed to cholecystectomy as soon as possible. We report the case of an elderly female patient who initially presented as having an acute coronary syndrome then was found intraoperatively to have GV, and discuss clinical points of the disease.